1995
DOI: 10.1108/14635789510088627
|View full text |Cite
|
Sign up to set email alerts
|

Current valuation practice in Australia

Abstract: The approaches used by valuers in assessing the market value of investment property are explained with reference to a survey of practising valuers in Australia. The survey examined the profile of the valuers, their interpretation of market value in a volatile market and details of the valuation methodology used for urban investment property. Identifies the cross‐tabulations between valuation qualifications, experience and methodology. The need for greater market research and a specialist group of valuers with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 1 publication
3
11
0
Order By: Relevance
“…As presented in Table II, the majority of (65.6 per cent) of the valuers work in the capital cities such as Sydney, Melbourne, Brisbane, etc., which is almost double the number of valuers (34.4 per cent) practising in non-capital cities. These findings are in line with Boyd (1995), and this distribution has been attributed to the fact that property market in the capital cities are larger and more liquid than non-capital areas (Deloitte Australia, 2018). In addition, there is a higher demand for valuation service, such as for transaction, mortgage, borrowing, taxation, merger and acquisition in larger cities (Mooya, 2011).…”
Section: Resultssupporting
confidence: 78%
See 4 more Smart Citations
“…As presented in Table II, the majority of (65.6 per cent) of the valuers work in the capital cities such as Sydney, Melbourne, Brisbane, etc., which is almost double the number of valuers (34.4 per cent) practising in non-capital cities. These findings are in line with Boyd (1995), and this distribution has been attributed to the fact that property market in the capital cities are larger and more liquid than non-capital areas (Deloitte Australia, 2018). In addition, there is a higher demand for valuation service, such as for transaction, mortgage, borrowing, taxation, merger and acquisition in larger cities (Mooya, 2011).…”
Section: Resultssupporting
confidence: 78%
“…A similar situation is obtainable in Nigeria and South Africa (Abidoye and Chan, 2016; Mooya, 2015), which can be interpreted that doctoral degree holders tend to pursue an academic career rather than being a valuation practitioner. Boyd (1995) found that 73 per cent of Australian property valuers had undergraduate certificates or associate diplomas, and only 6 per cent of them had postgraduate qualifications. The academic qualification of valuation practitioners in Australia has improved to a large extent over the last 20 years.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations